Recognition and disclosure of environment maintenance activity PT. Pertamina Geothermal Energy - Achmad Yanuar Irwan; Anak Agung Gde Satia Utama (Journal of Economics, Business, and Accountancy Ventura, 2018)
Global warming, climate change, carbon emissions, disaster, threatened species, waste, etc are externalities of growth and development of the industries and human activities and needs. Sustainable Development is a concept that is offered to achieve balance and sustainability. Company as one of the contributors in environmental damage responds it by corporate social responsibility and environmental management system. This study aims to explore the implementation of environmental accounting for sustainable value creation and explore the recognition and disclosure of the maintenance activities within the PT. Pertamina Geothermal Energy (PGE). The research method is qualitative exploratory. The results show that the company has been carrying out various environmental activities either directly or indirectly related to the production process. Accountability for the implementation of these activities encourage creating sustainable added value for the company. PGE perform recognition and disclosure of environmental activities and costs according to the principles of environmental accounting and PSAK No. 33. PGE has environmental income from the sale of carbon credits CDM’s program is recognized as other income. In addition, PGE has been compiled Sustainability Report according to the guidelines of Global Reporting Initiative (GRI).